KEUNTUNGAN INDUSTRI KERIPIK USUS AYAM PADA U.D ROHMAN FRIED CHIKEN - Dewa Ayu Saras Dewi; I Ketut Arnawa; Nyoman Utari Vipriyanti (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2022)
Chicken intestine chips are a typical food and if they are made more attractive and created with various flavors, the selling price will increase. This study aims to analyze the cost, acceptance, and profit as well as to describe the constraints faced by the chicken intestine chips industry in Indonesia. UD Rohman Fried Chicken, in Pamogan Village, South Denpasar District, Denpasar City. This research was conducted from October to December 2021. The respondents used were 5 people. The types of data used in this study were qualitative and quantitative, with the data sources used were primary and secondary data. The data collection method was through observation, interviews, questionnaires, and documentation. The data analysis used was cost and revenue analysis, and profit analysis. The results of this study indicate that the cost incurred in one production process for the chicken intestine chips industry at UD Rohman Fried Chiken in Pemogan Village, South Denpasar District, Denpasar City is Rp.2,631,454, while the receipt is Rp.4.225,000 per production process. with a total production of 97.5 kg, or 65 balls for one production process with a weight of 1.5 kg per ball. The profit received by the chicken intestine chips industry at U.D Rohman Fried Chicken in Pemogan Village, South Denpasar District, Denpasar City is Rp. 1,593,546 per production process. Constraints faced by the chicken intestine chips industry at U.D Rohman Fried Chicken in Pemogan Village, South Denpasar District, Denpasar City from an economic point of view, namely the problem of raw materials and, social constraints, technical constraints. However, it can be suggested to the Chicken Intestine Chips Industry at UD Rohman Fried Chiken, it is hoped that it will maintain the profits obtained by paying attention to the supply of raw materials in order to get more optimal results and it is hoped that the Chicken Intestine Chips Industry at UD Rohman Fried Chicken in Pemogan Village, District South Denpasar, Denpasar City in order to be able to maintain the quality and quantity of production so that they can compete in the market.